2002
DOI: 10.1016/s1534-5807(02)00148-x
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B Regulates Leptin Signal Transduction In Vivo

Abstract: Mice lacking the protein-tyrosine phosphatase PTP1B are hypersensitive to insulin and resistant to obesity. However, the molecular basis for resistance to obesity has been unclear. Here we show that PTP1B regulates leptin signaling. In transfection studies, PTP1B dephosphorylates the leptin receptor-associated kinase, Jak2. PTP1B is expressed in hypothalamic regions harboring leptin-responsive neurons. Compared to wild-type littermates, PTP1B(-/-) mice have decreased leptin/body fat ratios, leptin hypersensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
588
3
19

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 749 publications
(633 citation statements)
references
References 35 publications
23
588
3
19
Order By: Relevance
“…This effect was mimicked by stimulation of PTP1B ϩ/ϩ and PTP1B Ϫ/Ϫ primary hepatocytes with TNF-␣ or IL-6 or transfection of murine or HuH-7 human liver cells with PTP1B siRNA, indicating that hepatocytes lacking this phosphatase are hypersensitive to cytokine-mediated signaling. Although leptin-induced phosphorylation of the Tyr705 residue of STAT3 is de-phosphorylated by PTP1B, 17 in this study we reported, for the first time to our knowledge, a new substrate for PTP1B, the Tyr185 residue of JNK. We excluded the possibility of indirect effects of PTP1B deficiency, such as the up-regulation of dual-specificity phosphatase-9 (MKP-4/DUSP-9), 41 because its expression in the liver does not differ between PTP1B ϩ/ϩ and PTP1B Ϫ/Ϫ mice (results not shown).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…This effect was mimicked by stimulation of PTP1B ϩ/ϩ and PTP1B Ϫ/Ϫ primary hepatocytes with TNF-␣ or IL-6 or transfection of murine or HuH-7 human liver cells with PTP1B siRNA, indicating that hepatocytes lacking this phosphatase are hypersensitive to cytokine-mediated signaling. Although leptin-induced phosphorylation of the Tyr705 residue of STAT3 is de-phosphorylated by PTP1B, 17 in this study we reported, for the first time to our knowledge, a new substrate for PTP1B, the Tyr185 residue of JNK. We excluded the possibility of indirect effects of PTP1B deficiency, such as the up-regulation of dual-specificity phosphatase-9 (MKP-4/DUSP-9), 41 because its expression in the liver does not differ between PTP1B ϩ/ϩ and PTP1B Ϫ/Ϫ mice (results not shown).…”
Section: Discussioncontrasting
confidence: 49%
“…Similarly, PTP1B reduced IL-6 -induced phosphorylation of Tyr705 residue of STAT3, a well-known substrate of this phosphatase. 17 …”
Section: Ptp1b Decreased Tnf-␣-induced Jnk Phosphorylation In Human Amentioning
confidence: 99%
See 1 more Smart Citation
“…2). Protein-tyrosine phosphatase 1B, a well-known inhibitor of insulin action, also terminates leptin signaling through inactivation of JAK2 (35). Leptin acting through LRb has also been demonstrated to regulate insulin receptor substrate 1 and 2, mitogen-activated protein kinase, extracellular-regulated kinase, Akt, and phosphatidylinositol 3-kinase in the hypothalamus, raising the possibility of cross-talk between leptin and insulin (36).…”
Section: Leptinmentioning
confidence: 99%
“…Other factors implicated in leptin resistance in the brain include reduction in leptin transport across the bloodbrain barrier, induction of protein tyrosine phosphatase 1B activity, and dysregulation of neuropeptides (3,35). Collectively, these abnormalities increase appetite and weight, albeit to a lesser degree than congenital leptin deficiency (4).…”
Section: Role Of Leptin In Famine and Feastmentioning
confidence: 99%